2005
DOI: 10.1002/cbic.200500141
|View full text |Cite
|
Sign up to set email alerts
|

Protein Flexibility and Ligand Rigidity: A Thermodynamic and Kinetic Study of ITAM‐Based Ligand Binding to Syk Tandem SH2

Abstract: The Syk tandem Src homology 2 domain (Syk tSH2) constitutes a flexible protein module involved in the regulation of Syk kinase activity. The Syk tSH2 domain is assumed to function by adapting the distance between its two SH2 domains upon bivalent binding to diphosphotyrosine ligands. A thermodynamic and kinetic analysis of ligand binding was performed by using surface plasmon resonance (SPR). Furthermore, the effect of binding on the Syk tSH2 structural dynamics was probed by hydrogen/deuterium exchange and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…The apparent equilibrium dissociation constant of tSH2 and ITP is expected to be substantially lower than the limits achieved here. Reported values for the apparent K d are ~0.001 to 30 nM from other methods, 1116 which is higher affinity than can be determined by direct NMR measurements. 41 …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The apparent equilibrium dissociation constant of tSH2 and ITP is expected to be substantially lower than the limits achieved here. Reported values for the apparent K d are ~0.001 to 30 nM from other methods, 1116 which is higher affinity than can be determined by direct NMR measurements. 41 …”
Section: Resultsmentioning
confidence: 83%
“…18 The conformational effect of phosphorylation is of considerably greater magnitude than the flexibility previously described for unphosphorylated Syk. 16 It was suggested that the allosteric inhibition of the Syk-receptor interaction by IA phosphorylation was through a conformational change in domain structure that switched the bifunctional high-affinity binding across two SH2 domains to a monofunctional lower-affinity binding that involved only one SH2 domain. 18 Thus, linker A phosphorylation was proposed to restrict the separation and relative orientation of two SH2 domains in a manner that no longer appropriately positioned the two phosphotyrosine binding sites to allow bifunctional binding, and therefore binding is by a single pYXX(I/L) cassette and the affinity for ITAM is reduced to a value comparable to a single SH2 domain.…”
Section: Introductionmentioning
confidence: 99%
“…EV peptide inhibited STATb phosphorylation far better than the Y845 sequence (Figure 1a). This result is not surprising; the natural Y845 domain may assume a favorable conformation only when the sequence is constrained by the context flanking sequences [3031]. Although EV was active in inhibiting the phosphorylation of STAT5b, the peptide affinity was not particularly high (IC 50 = 2.5 μM).…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to significant improvements in binding affinity. Of course, even where this rigidity is built into the small molecule, the entropic advantage may not always be realised as decreases in protein flexibility may still dominate [58] . The free energy, of course, is composed of the enthalpy and entropy terms and the different types of interaction often have individual thermodynamic signatures ( Figure 4 ).…”
Section: Lead Optimisation and Mechanism Of Action Studiesmentioning
confidence: 98%